Case report: An atypical case of uterine adenosarcoma with extensive bizarre stromal cells and amplification of MDM2 - Xiao, Xiaoling; He, Ying (Frontiers in Oncology, 2024)
Polypoid lesions in the uterus are very common. There are a lot of benign lesions and malignant tumor should be considered. Adenosarcoma, one of the differential diagnoses, is a rare mixed epithelial and mesenchymal tumor consisting of benign epithelial components and sarcoma stroma. Here, we present a case of atypical adenosarcoma that has never been reported. This tumor was composed of benign endometrial epithelium and hyperplastic stroma with extensive bizarre stromal cells.But the cleft-like spaces and papillary stomal fronds which were the typical histological images of adenosarcoma were absent. These stomal cells, including bizarre cells, were positive for vimentin, CD10, ER, PR, cyclin D1 and P16 but were immunonegative for caldesmon. Furthermore, this tumor harbored amplification of MDM2, as revealed by fluorescence in situ hybridization testing (FISH) and next-generation DNA sequencing (NGS).